Perancangan Animasi Interaktif Belajar Mengenal Huruf Hijaiyah Pada TKQ Al-Khoiriyah - Ida Rosmaidah; Henny Destiana (Universitas Bina Sarana Informatika, 2017)
Instructional media that rely on stationery such as books, paper, pencil or pen in the teaching-learning process causes launch the lack of communication between parents and teachers with children or students. Hijaiyah letter is a letter of the Qur'an and is written using the Arabic alphabet. In this case study media should be more creative in applying learning methods in order to increase interest in learning at an early age especially for toddlers learning to read science briefingbeforeproceeding to further education. With the interactive animation application is expected to provide benefits to children who we love. Instructional media presented certainly learn while playing with a purpose menumbuhan interest in learning and introducing information technology in children aged under five.